(untitled) (Ameghiniana, 2018)
In order to elucidate the effect that physico-chemical lake characteristics exert on diatom valve preservation, the taphonomic signatures of the target taxon Cyclotella meneghiniana Kützing was assessed in twenty five shallow lakes of the Pampa plain of Argentina. Fragmentation and dissolution indices were quantitatively related to environmental variables by means of univariate and multivariate techniques (Generalized Linear Models, Redundancy Analysis and Canonical Correspondence Analysis). Valves showed signs of fragmentation and dissolution, and different stages of taphonomic damage were recognized. Dissolution significantly increased with salinity, pH, carbonate and bicarbonate concentrations. Environmental constraints on valve fragmentation were less clearly identified in the dataset. Besides its key role on valve preservation, salinity also accounted for a significant, although lower, percentage of the variation in diatom composition of death assemblages. These results encourage the use of diatom taphonomy as an indicator of past salinity fluctuations in Pampean shallow lakes. Taphonomic profiles can be used to reconstruct past environmental fluctuations, as well as to identify assemblages subjected to significant taphonomic biases. Combining diatom taphonomy and community paleoecology constitutes a promising tool for maximizing their respective strengths while downweighing their limitations.